English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

find the derivative. (differenctiate)

2006-12-03 18:54:47 · 6 answers · asked by pago 1 in Science & Mathematics Mathematics

6 answers

1st: using the trigonometric identity sec x = 1/cos x, we simplify
f(x) as follows:
f(x) = sec x/(1 + sec x) = (1/cos x)/(1 + (1/cos x))
= 1/(1 + cos x)
2nd: differentiate the resulting expression for f(x) w.r.t. x:
f'(x) = (-1)(1 + cos x)^(-2)(-sin x)
f'(x) = (sin x)/(1 + cos x)^2

2006-12-03 19:14:20 · answer #1 · answered by JoseABDris 2 · 0 0

This differentiation is made both shorter and easier by first simplifying f(x):

f(x) = (1/cos x)/(1 + 1/cos x)

(Im presuming you meant to put braces around "1 + sec x"; it looks much better and much more suggestive for the next step when written out on the page with "____"symbols for division rather than "/".)

It simplifies to f(x) = 1/(1 + cos x) or (1 + cos x)^(-1)

This is now trivial to differentiate. We have:

df/dx = sin x /(1 + cos x)^2; that's it!

Note that there was no need to mess around with sec and tan x's, the combining of separate terms, or anything else as in the first responder's otherwise correct but more circuitous method. In addition, by using the squared form in the denominator above, the solution is written in its most compact form.

Live long and prosper.

2006-12-04 03:29:33 · answer #2 · answered by Dr Spock 6 · 0 0

OK Uber... braket mismatch.. I try again

sec/(1+sec)=1/(1+cos)

f'(x)=sin/(1+cos)²

2006-12-04 03:01:17 · answer #3 · answered by Champoleon 5 · 0 0

capital F as opposed to lower case f is usually used for a function that has been integrated already....

so usually,

F'(x) = f(x) meaning you just get the function on the right hand side.

2006-12-04 03:03:00 · answer #4 · answered by xian gaon 2 · 0 0

[(1+secx)(d/dx secx)-secx(d/dx(1+secx)]/(1=secx)^2
= [(1+secx)(secxtanx)-secx(secxtanx)]/(1+secx)^2
= [secxtanx+sec^2xtanx-sec^2xsecxtanx]/(1+secx)^2
=secxtanx/(1+secx)^2
=sinx/(1+cosx)^2

2006-12-04 03:24:43 · answer #5 · answered by c_arry 1 · 0 0

sec(x)*tan(x)/(1+sec(x))-sec(x)^2*tan(x)/(1+sec(x))^2
simplified it equals sin(x)/(cos(x)^2+2*cos(x)+1)
Do not listen to champ, sec = 1/cos but sec/1+sec = (1/cos)/(1+(1/cos)) not 1+cos/cos

2006-12-04 02:59:30 · answer #6 · answered by Uber_Ninja 1 · 0 0

fedest.com, questions and answers